2010
DOI: 10.1007/s11224-010-9645-3
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the tautomerism of 2,5-substituted diazoles

Abstract: Detailed investigation of the tautomerism of oxadiazoles, thiadiazoles, and selenadiazoles containing hydroxy, mercapto, or selenyl groups in position 2 and 5 of the five-membered ring was carried out at MP2, MP4, and CCSD(T) levels of theory. The relative stabilities of the tautomers of the heterocycles were investigated in gas phase. It is found that the dioxo form is the preferred tautomer if the exocyclic group is hydroxy. If the exocyclic group is mercapto or selenyl group the most stable tautomer is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The distance between the layers is 3.10 Å. In this context, it should be mentioned that Enchev and Angelove reported an ab initio study of the tautomerism of 1 (Figure ) and similar molecules, and it was concluded that tautomer 1a is preferred over 1b in accordance with our findings.…”
Section: Resultssupporting
confidence: 90%
“…The distance between the layers is 3.10 Å. In this context, it should be mentioned that Enchev and Angelove reported an ab initio study of the tautomerism of 1 (Figure ) and similar molecules, and it was concluded that tautomer 1a is preferred over 1b in accordance with our findings.…”
Section: Resultssupporting
confidence: 90%
“…38 Appearance of medium to weak bands at the range 582-524 cm -1 in IR spectrum can be related to stretching of 𝝊(C-Se) for the compounds (Z 3 A'-Z 3 C'). 39 1 HNMR and 13…”
Section: Infrared Spectra (Ft-ir)mentioning
confidence: 99%
“…In the theoretical by Enchev and Angelova [261], the tautomerism of oxadiazole, thiadiazole, and selenadiazole containing hydroxy, mercapto, or selenyl groups in positions 2 and 5 of the five-membered ring was investigated.…”
Section: Issuementioning
confidence: 99%